Analysing Idiomatic Expressions in Coldplay's Album “A Head Full of Dreams”: A Linguistic Perspective - Diyo, Muhammad Panji; Faisal, Faisal (Ma'soem University, 2025)
This analysis highlights the significance of understanding idiomatic language in music as a means of appreciating the complexity of human expression and creativity. This study investigates the idiomatic expressions found in Coldplay's album